2019
DOI: 10.3390/ma12030443
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection of Asphalt Concrete Using Piezo-Ultrasonic Wave Technology

Abstract: Asphalt concrete has been widely used in road engineering as a surface material. Meanwhile, ultrasonic testing technology has also been developed rapidly. Aiming to evaluate the feasibility of the ultrasonic wave method, the present work reports a laboratory investigation on damage detection of asphalt concrete using piezo-ultrasonic wave technology. The gradation of AC-13 was selected and prepared based on the Marshall’s design. The ultrasonic wave velocities of samples were tested with different environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Next, ultrasonic testing was carried out on these specimens and the dynamic moduli of the asphalt concrete samples were calculated using Equation (1), based on ultrasonic wave velocity, density, and Poisson's ratio. Wave velocity is an acoustic parameter which was found to correlate well with mechanical properties, such as elastic moduli, and volumetric properties, such as in-place field density [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, ultrasonic testing was carried out on these specimens and the dynamic moduli of the asphalt concrete samples were calculated using Equation (1), based on ultrasonic wave velocity, density, and Poisson's ratio. Wave velocity is an acoustic parameter which was found to correlate well with mechanical properties, such as elastic moduli, and volumetric properties, such as in-place field density [1].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of longitudinal waves, particle vibration occurs in the direction parallel to the wave propagation, whereas for shear waves, particles vibrate in the direction perpendicular to the wave propagation. Acoustic parameters, like amplitude, wave velocity, and wave frequency, are directly related to the mechanical properties of the medium [1]. Thus, in a solid elastic isotropic medium, these waves are related to the elastic modulus (E), Poisson's ratio (ν), and density (ρ), based on the given equations below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the literature that presented the use of NDT in different applications such as to find a defect in polymers and a metallic structure [33]. Among the available methods of NDT, ultrasonic pulse velocity has been effectively used for the detection of cracks in a concrete structure for many decades but in the literature, the use of this technology is not too much in the testing asphalt concrete [34][35][36]. The time of travel is measured electronically with a device when the ultrasonic wave is passed through the specimen.…”
Section: Ultrasonic Pulse Velocity Testmentioning
confidence: 99%
“…Field investigation is the principal requirement to ensure safe and well-accepted driving conditions in pavement maintenance. In the study by Pan et al [30], piezo-ultrasonic wave technology was used for damage detection, including groove damage and cylinder cutting damage, in road engineering. Pan found that factors such as temperature, defect size, and ultrasonic velocity would affect the detection accuracy.…”
mentioning
confidence: 99%